The linear-ordered collagen scaffold-BDNF complex significantly promotes functional recovery after completely transected spinal cord injury in canine. (February 2015) - Han, Sufang; Wang, Bin; Jin, Wei; Xiao, Zhifeng; Li, Xing; Ding, Wenyong; Kapur, Meghan; Chen, Bing; Yuan, Baoyu; Zhu, Tiansheng; Wang, Handong; Wang, Jing; et al.
Abstract: Spinal cord injury (SCI) is still a worldwide clinical challenge for which there is no viable therapeutic method. We focused on developing combinatorial methods targeting the complex pathological process of SCI. In this study, we implanted linear-ordered collagen scaffold (LOCS) fibers with collagen binding brain-derived neurotrophic factor (BDNF) by tagging a collagen-binding domain (CBD) (LOCS + CBD-BDNF) in completely transected canine SCI with multisystem rehabilitation to validate its potential therapeutic effect through a long-term (38 weeks) observation. We found that LOCS + CBD-BDNF implants strikingly promoted locomotion and functional sensory recovery, with some dogs standing unassisted and transiently moving. Further histological analysis showed that administration of LOCS + CBD-BDNF reduced lesion volume, decreased collagen deposits, promoted axon regeneration and improved myelination, leading to functional recovery. Collectively, LOCS + CBD-BDNF showed striking therapeutic effect on completely transected canine SCI model and it is the first time to report such breakthrough in the war with SCI. Undoubtedly, it is a potentially promising therapeutic method for SCI paralysis or other movement disorders caused by neurological diseases in the future.